Mathematics Learning with Guided Inquiry Model Open-Oriented Problem Solving Improves Student Learning Outcomes - Purwati, Gusti Ayu Made; Sudana, Dewa Nyoman; Arini, Ni Wayan (Universitas Pendidikan Ganesha, 2020)
The low learning outcomes of mathematics are due to students' mathematics lesson problems' lack of optimal solving. One of the ways is by using a guided inquiry learning model with an open problem-solving orientation. This research aimed to determine the guided inquiry learning model's effect with open problem-solving orientation on fourth-grade elementary school students' mathematics learning outcomes. This type of research is an experimental design with a non-equivalent post-test only control group design. The study population was 180 students. The research sample was 23 students (experimental) and 23 students (control). The research sample was taken using a simple random sampling technique. The method used in collecting data on mathematics learning outcomes was a test in an essay consisting of 5 items. The data collected were mathematics learning outcomes and were analyzed using t-test. The study results were getting an average post-test result in the experimental group of 18.17 and 11.04 in the control group after being given treatment. The t-test results obtained by t-count greater than t-table (17,825> 1,680). From the results of the t-test analysis and the average learning outcomes, it can be concluded that the guided inquiry learning model with open problem-solving orientation affects the mathematics learning outcomes of fourth-grade elementary school students. This research implies that it can increase students' concentration in learning activities to foster innovative learning and add new experiences.